PKC‐mediated inhibitory feedback of the cholecystokinin 1 receptor controls the shape of oscillatory Ca2+ signals. (13th April 2015) - Willems, Peter H. G. M.; Pahle, Jürgen; Stalpers, Xenia L.; Mugahid, Douaa; Nikolaew, Alexander; Koopman, Werner J. H.; Kummer, Ursula
<x xml:space="preserve">Abstract</x> Translation of extracellular hormonal input into cellular responses is often mediated by repetitive increases in cytosolic free Ca2+ concentration ([Ca2+]c). Amplitude, duration and frequency of these so‐called [Ca2+]c oscillations then carry information about the nature and concentration of the extracellular signalling molecule. At present, there are different hypotheses concerning the induction and control of these oscillations. Here, we investigated the role of agonist‐induced receptor phosphorylation in this process using Chinese hamster ovary cells stably expressing a variant of the cholecystokinin 1 receptor (CCK1R) lacking the four consensus sites for protein kinase C (PKC) phosphorylation and deficient in CCK‐induced receptor phosphorylation (CCK1R‐mt cells). In the presence of cholecystokinin‐(26‐33)‐peptide amide (CCK‐8), these cells displayed Ca2+ oscillations with a much more pronounced bursting dynamics rather than the dominant spiking dynamics observed in Chinese hamster ovary cells stably expressing the wild‐type CCK1R. The bursting behaviour returned to predominantly spiking behaviour following removal of extracellular Ca2+, suggesting that CCK‐8‐induced, PKC‐mediated CCK1R phosphorylation inhibits Ca2+ influx across the plasma membrane. To gain mechanistic insight into the underlying mechanism we developed a mathematical model able to reproduce the experimental observations. From the model we conclude that binding of CCK‐8 to the CCK1R leads to activation of PKC which subsequently phosphorylates the receptor to inhibit the receptor‐mediated influx of Ca2+ across the plasma membrane. Receptor‐specific differences in this feedback mechanism may, at least in part, explain the observation that different agonists evoke [Ca2+]c oscillations with different kinetics in the same cell type.